‘I’VE CHANGED’ SAYS SOUTH AFRICAN LAW: HAS THE JUDICIARY OPENED UP TO BLACK WOMEN LAWYERS? (The Pretoria Student Law Review, 2021)
Historically, South African law and legal culture has been an exclusionary field towards a number of different groups of people. One of the most glaring of these exclusions is that of black women lawyers. South African law and politics have claimed to have changed, but one still finds spaces that have not quite had the substantial kind of change that would be in line with the transformative nature that our constitution demands or at the very least, there is still plenty of room for improvement. The 2017/2018 statistics from the Law Society of South Africa (LSSA)1 paints a clear picture of the past and current legal spheres. I will also rely on some sentiments that I have read from a number of black women scholars in legal practice to give the perspective to what working as a black women lawyer in South Africa is like.
Keywords: black women lawyers; legal practice; South Africa